Parental allergic disease before and after child birth poses similar risk for childhood allergies. Issue 7 (25th March 2015) - Fuertes, E.; Standl, M.; von Berg, A.; Lehmann, I.; Hoffmann, B.; Bauer, C.‐P.; Koletzko, S.; Berdel, D.; Heinrich, J.
Abstract Whether the strength of associations between parental and child allergic diseases differs by whether the first onset of the parental disease is before or after a child's birth has never been examined and is the aim of this study. Yearly childhood asthma, allergic rhinitis, and eczema diagnoses were longitudinally regressed against the effect of a parental disease (pre‐ vs post‐child birth) of the same type separately for each parent using generalized estimation equations. Both a maternal and paternal history of asthma were associated with childhood asthma prevalence up to 15 years of age. Effect estimates were similar for parental asthma with first onset before and after the birth of the child. The results for allergic rhinitis and eczema were less consistent. Parental allergic diseases with first onsets before and after the birth of a child both pose risks to childhood allergic disease in the offspring, especially for asthma.